Land inventory as the instrument for development of amalgamated territorial communities in Ukraine - Roman Kuryltsiv; Józef Hernik; Nadiia Kryshenyk; Nataliya Zhydovska (Acta Scientiarum Polonorum. Formatio Circumiectus)
The scientific article reveals peculiarities of the new administrative-territorial organization under conditions of decentralization of power in Ukraine, highlights the main stages of establishment of amalgamated territorial communities, conditions of the existing and future formation of them. It is argued that efficient development of corresponding territories requires financial decentralization and cession of agricultural land parcels of state ownership to communal holding. The research presents an algorithm of cession of agricultural lands of state ownership to communal possessing by corresponding amalgamated territorial communities. Such step will supply formation of clear and transparent revenue of local budgets in terms of payment for lands and will stimulate economic development of amalgamated territorial communities. It is confirmed that inventory of land should become one of the key instruments of the further development of amalgamated territorial communities, because cession of state-owned agricultural land parcels to communal possessing by corresponding communities will secure improvement of economic development of the amalgamated territorial communities, as well as will attract investments.